Wīdithat chut "kro̜ kan phai yāsēptit" (Samnak Phatthanā Kānpō̜ngkan læ Kǣkhai Panhā Yāsēptit, Samnakngān Pō̜. Pō̜. Sō̜., 2013)
Promotion of preventing narcotic addiction via family understanding, Buddhist teachings, and knowledge about drug addiction.